Temperature dissimilarity drives flower–visitor interaction turnover across elevation in the Mexican Transition Zone - Pedro Luna; Fabricio Villalobos; Federico Escobar; Frederico Neves; Gonzalo Castillo‐Campos; Ismael Hinojosa‐Díaz; Luciano Cagnolo; Ek del‐Val; Maurice Leponce; Wesley Dáttilo (Journal of Biogeography, 2023)
Aim Most biodiversity studies have considered species to be isolated entities, neglecting the fact that their biotic interactions and spatial variation are fundamental to their persistence across elevational gradients. Here, using a standardized sampling methodology, we evaluated how and why the composition of flower–visitor interactions (i.e. beta diversity) varies over an extensive elevational gradient. Specifically, we aimed to identify which biotic (species turnover) and abiotic factors (temperature, precipitation and primary productivity) inherent to elevational gradients can explain the distribution of floral visitor–plant interactions. Location Mexican Transition Zone. Taxon Angiosperms, Hymenoptera, Lepidoptera, Diptera, Hemiptera and Coleoptera. Methods We sampled ecological interactions between floral visitors and flowering plants at 10 sites along an elevational gradient from 4 to 3425 m.a.s.l. We measured the additive partitioning of the beta diversity of species interactions and used generalized dissimilarity modelling to assess how spatial and environmental factors can explain the observed dissimilarity. Results We found that the composition of interactions between floral visitors and plant species differs from lowlands to highlands mainly due to differences in temperature across the studied elevation gradient, rather than geographical distance or other environmental factors (i.e. mean annual precipitation and net primary productivity). We also observed that the main component of the beta diversity of interactions was interaction turnover driven by the turnover of both plants and floral visitors along the elevation gradient studied, which may be influenced by both temperature and the biogeographical affinity of biotas. Main Conclusions We conclude that environmental filters play a crucial role in the establishment of novel interactions, as temperature can filter species and impact the behaviour and traits of floral visitors and plants across an elevational gradient. These findings underscore the importance of considering the role of abiotic factors in predicting and explaining the distribution of species interactions across different elevational gradients.